Changes of Peripheral Nerve Function and Vitamin B12 Level in People With Parkinson's Disease - Qiu, Feng; Wu, Yue; Cao, Hui; Liu, Ben; Du, Mingyang; Jiang, Haibo; Li, Shun (Frontiers in Neurology, 2020)
Background and Purpose: Peripheral nerve function plays an important role in balance control. Impairment of peripheral sensory information appears in People with Parkinson’s disease (PD). Furthermore, there is a link between peripheral nerve disorders and vitamin B12 level. Here we studied whether there were deficits of peripheral nerve function and vitamin B12 level, which may lead to decreased postural stability in PD. Methods: Fifty PD and 50 age-matched healthy subjects were enrolled in the study. This study evaluated folic acid and vitamin B12 levels in serum. Postural balance was studied according to clinical Tinetti scale. Some comprehensive physiological assessments of peripheral nerve functions, including peripheral sensation, the perception of temperature, pain and touch sensations were undertaken in this study. Results: Compared to control group, vitamin B12 and folic acid were decreased in PD (P<0.05). PD group demonstrated declines in peripheral nerve functionst, including touch, temperature, pain and nerve conduction velocity (P<0.05). Furthermore, significant association was noticed between decreased peripheral nerve function and low Tinetti scale (P<0.05). Low vitamin B12 levels were associated with deficits of peripheral nerve function and poor balance in PD (P<0.05). Conclusions: Data suggested that peripheral nerve function was impaired in people with Parkinson’s disease. Deficits of sensory input and low vitamin B12 level may lead to decline in clinical balance in PD.